SCOPE OF EDUCATIONAL MANAGEMENT AS A FOUNDATION FOR DEVELOPING THE QUALITY AND EFFECTIVENESS OF INSTITUTIONS - Umayah Umayah; Ridotul Inayah; Anis Zohriah; Apud Apud (Jurnal Konseling Pendidikan Islam, 2026)
Educational management is a systematic process encompassing planning, organizing, implementing, and supervising all educational resources to ensure the effective and efficient achievement of objectives. The scope of educational management is broad, encompassing curriculum management, student management, development of teaching and educational staff, management of facilities and infrastructure, financial governance, school administration, and public relations. This article aims to provide a comprehensive overview of the scope of educational management as a fundamental foundation for developing the quality and increasing the effectiveness of educational institutions. The research method used is a literature review, synthesizing theoretical perspectives and empirical findings from various previous studies. The results of the study indicate that structured, integrated, and coordinated educational management practices play a crucial role in strengthening institutional performance, encouraging innovation in the learning process, and ensuring the sustainability of educational development. Furthermore, effective educational management contributes to the creation of a conducive academic environment, supporting the professional growth of educators, and increasing public and stakeholder trust in educational institutions. In conclusion, the scope of educational management not only functions to achieve short-term educational goals but also serves as a strategic pillar in building institutional resilience, increasing competitiveness, and ensuring the quality of education in a sustainable manner.